Genetic and neuro-epigenetic effects of divergent artificial selection for feather pecking behaviour in chickens - Elske N. de Haas; Fábio Pértille; Joergen B. Kjaer; Per Jensen; Carlos Guerrero-Bosagna (BMC Genomics)
Abstract Feather pecking (FP) is a repetitive behaviour in chickens, influenced by genetic, epigenetic, and environmental factors, similar to behaviours seen in human developmental disorders (e.g., hyperactivity, autism). This study examines genetic and neuro-epigenetic factors in the thalamus of chickens from lines selected for seven generations for high or low FP behaviour (HFP or LFP). We integrate data on Differentially Methylated Regions (DMRs), Single Nucleotide Polymorphisms (SNPs), and Copy Number Variations (CNVs) in this controlled artificial selection process. Significant differences in behaviour, immunology, and neurology have been reported in these lines. We identified 710 SNPs in these lines that indicate new potentially important genes for FP such as TMPRSS6 (implicated in autism), and SST and ARNT2 (somatostatin function). CNV were the omic level most affected during selection. The largest CNVs found were in RIC3 (gain in HFP) and SH3RF2 (gain in LFP) genes, linked to nicotinic acetylcholine receptor regulation and human oncogenesis, respectively. Our study also suggests that promoters and introns are hotspots for CpG depletion. The overlapping of the omic levels investigated here with data from a public FP Quantitative Trait Loci (QTL) database revealed novel candidate genes for understanding repetitive behaviours, such as RTKN2, associated with Alzheimer’s disease in humans. This study suggests CNVs as a crucial initial step for genomic diversification, potentially more impactful than SNPs.